Clinical, Microbiological, and Genetic Characteristics of Heteroresistant Vancomycin-Intermediate Staphylococcus aureus Bacteremia in a Teaching Hospital - Di Gregorio, Sabrina Noelia (2014)
The emergence of vancomycin intermediate Staphylococcus aureus (VISA) and heterogeneous VISA (hVISA) is of major concern worldwide. Our objective was to investigate the prevalence, phenotypic and molecular features of hVISA strains isolated from bacteremic patients and to determine the clinical significance of the hVISA phenotype in patients with bacteremia. A total of 104 S. aureus blood isolates were collected from a teaching hospital of Argentina between August 2009 and November 2010. No VISA isolate was recovered, and 3 out of 92 patients (3.3%) were infected with hVISA, 2 of them methicillin-resistant S. aureus (MRSA) (4.5% of MRSA). Macro Etest and prediffusion method detected 3/3 and 2/3 hVISA respectively. Considering the type of bacteremia, the three cases were distributed as follows: two patients had suffered multiple episodes of bacteremia (both hVISA strains recovered in the second episode), while only one patient had suffered a single episode of bacteremia with hVISA infection. MRSA bloodstream isolates exhibiting the hVISA phenotype were related to HA-MRSA Cordobes clone (ST5-SCCmec I-spa t149) and MRSA Argentinean pediatric clone (ST100-SCCmec IVNV-spa t002), but not to CA-MRSA-ST30-SCCmec IV-spa t019 clone that was one of the most frequent in our country. Although still relatively infrequent in our hospital, hVISA strains were significantly associated with multiple episodes of bacteremia ( p = 0.037) and genetically unrelated.